Early childhood caries management using fluoride varnish and neutral fluoride gel: a randomized clinical trial - Geovanna Peres de SOUSA; Cacilda Castelo Branco LIMA; Mariana Minatel BRAGA; Lúcia de Fátima Almeida de Deus MOURA; Marina de Deus Moura de LIMA; Marcoeli Silva de MOURA (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The aim of this study was to evaluate the clinical efficacy of varnish and neutral fluoride gel in the management of early childhood caries (ECC). A randomized clinical trial was conducted to compare two strategies for ECC management: topical application of neutral fluoride gel (NFG group) and varnish (FV group) every four months for a period of one year. The sample consisted of children between the ages of three and four years, enrolled in public daycare centers. The incidence of ECC between the groups was compared by assessing values (new dmfs) at two levels: d2 when enamel/dentin were affected and d3 when dentin affected. Pearson's Chi-square, Fisher's Exact, Kolmogorov-Smirnov and Mann-Whitney tests were used to compare the incidence and increment of caries between the NFG and FV groups (p<0.05). A total of 240 children were included in this study and 213 children (88.7%) were followed up for 12 months. The incidence of ECC was 24.1% in the GF and 21.0% in the FV groups (p=0.586). The increment of caries in d2mfs was 1.36 (95% CI = 0.83 - 1.89) in the NFG and 1.33 (95% CI = 0.75 - 1.89) in FV (p=0.756) groups. Increment of caries in d3mfs was 1.60 (95% CI = 0.95 - 2.25) in NFG and 1.40 (95% CI = 0.75 - 2.04) in FV (p=0.468). Neutral fluoride gel and fluoride varnish exhibited similar efficacy in the management of ECC after 12 months of follow-up.